On-Pump Beating Heart Versus Conventional Coronary Artery Bypass Grafting Early After Myocardial Infarction: A Propensity-Score Matched Analysis From the ANZSCTS Database - Zhu, M.; Huq, M.; Billah, B.; Tran, L.; Reid, Christopher; Varatharajah, K.; Rosenfeldt, F. (Elsevier, 2018)
Background: Coronary artery bypass grafting (CABG) performed early after acute myocardial infarction (AMI) carries a high risk of mortality. By avoiding cardioplegic arrest and aortic cross-clamping, on-pump beating heart CABG (ONBEAT) may benefit patients requiring urgent or emergency revascularisation in the setting of AMI. We evaluated the early and long-term outcomes of ONBEAT versus conventional CABG (ONSTOP) utilising the ANZSCTS National Cardiac Surgery Database. Methods: Between 2001 and 2015, 5851 patients underwent non-elective on-pump CABG within 7 days of AMI. Of these, 77 patients (1.3%) underwent ONBEAT and 5774 (98.7%) underwent ONSTOP surgery. Propensity-score matching (with a 1:2 matching ratio) was performed for risk adjustment. Survival data were obtained from the National Death Index. Results: Before matching, the unadjusted 30-day mortality was ONBEAT: 9/77 (11.7%) vs. ONSTOP: 256/5774 (4.4%), p < 0.001. Preoperative factors independently associated with the ONBEAT were: septuagenarian age, peripheral vascular disease, redo surgery, cardiogenic shock, emergency surgery and single-vessel disease. After propensity-score matching, 30-day mortality was similar (ONBEAT: 9/77 (11.7%) vs. ONSTOP: 16/154 (10.4%), p = 0.85), as was the rate of major adverse cardiac and cerebrovascular events (ONBEAT: 17/77 (22.1%) vs. ONSTOP: 38/154 (24.7%), p = 0.84). ONBEAT patients received fewer distal anastomoses and were more likely to have incomplete revascularisation (ONBEAT: 15/77 (19.5%) vs. ONSTOP: 15/154, (9.7%), p = 0.03). Despite this, 12-year survival was comparable (ONBEAT: 64.8% (95% CI 39.4-82.4%) vs. ONSTOP: 63.6% (95% CI 50.5, 74.3%), p = 0.89). Conclusions: ONBEAT can be performed safely in high-risk patients requiring CABG early after AMI with similar short and long-term survival compared to ONSTOP.